2024
DOI: 10.1007/s00125-024-06089-5
|View full text |Cite
|
Sign up to set email alerts
|

Assisting the implementation of screening for type 1 diabetes by using artificial intelligence on publicly available data

Pedro F. Teixeira,
Tadej Battelino,
Anneli Carlsson
et al.

Abstract: The type 1 diabetes community is coalescing around the benefits and advantages of early screening for disease risk. To be accepted by healthcare providers, regulatory authorities and payers, screening programmes need to show that the testing variables allow accurate risk prediction and that individualised risk-informed monitoring plans are established, as well as operational feasibility, cost-effectiveness and acceptance at population level. Artificial intelligence (AI) has the potential to contribute to solvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Recently, the question of screening has become a highly topical issue as it has been shown that Teplizumab can postpone the diagnosis of type 1 diabetes [22] and this treatment has been approved by Food and Drug Administration in USA. In several areas screening of the general population has started and new methods using big data and artifical intelligence to improve prediction has been proposed [23]. It is relevant to investigate the view of adults in the general population on screening, and also of the children themselves, not least in families without specific genetic risk of getting the disease and with no family history of type 1 diabetes and therefore most often low awareness of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the question of screening has become a highly topical issue as it has been shown that Teplizumab can postpone the diagnosis of type 1 diabetes [22] and this treatment has been approved by Food and Drug Administration in USA. In several areas screening of the general population has started and new methods using big data and artifical intelligence to improve prediction has been proposed [23]. It is relevant to investigate the view of adults in the general population on screening, and also of the children themselves, not least in families without specific genetic risk of getting the disease and with no family history of type 1 diabetes and therefore most often low awareness of diabetes.…”
Section: Introductionmentioning
confidence: 99%